ANALISIS PENGARUH BIMBINGAN KONSELING BERBASIS PENDIDIKAN ISLAM DALAM MEREDUKSI PERILAKU BULLYNG PADA SISWA - Yulianti Yulianti; Rasikha Aulia Putri; Anggie Resa Safitri; Iftitah Awaliyah; Zahara Litasya; Hernita Khairunnisya; Haliza Nurika (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Bullying behavior is a serious issue in the world of education, including in Indonesia. Studies show that repeated exposure to bullying can negatively impact students' mental health and well-being. In Indonesia, the prevalence of bullying behavior among students reaches quite high levels, involving various forms such as teasing, insults and beatings. The Indonesian Child Protection Commission (KPAI) identifies bullying in schools as a serious form of violence, although in some cases society sometimes considers it normal. Handling bullying behavior requires an active role from the school, including through counseling guidance services. Islamic guidance is recognized as a method that can help reduce bullying behavior by focusing on the principles of the Islamic religion, emphasizing the happiness of life in this world and the afterlife. The objectives of Islamic guidance include helping individuals solve problems, preventing problems from arising, and guiding individuals in implementing the teachings of the Islamic religion. Islamic education also emphasizes the prohibition against bullying behavior, considering it a disgraceful or negative act. Low empathy was identified as another contributor to bullying behavior, and Islamic guidance was considered an important effort in creating quality students. A holistic approach that integrates religious values and guidance and counseling services is expected to help reduce incidents of bullying behavior among students. Future research can further explore the implementation of guidance and counseling programs that collaborate with religious and Islamic education. A deeper analysis of the role of religious guidance in changing personality characteristics associated with bullying is also an important focus. Including the experiences of students, teachers, counselors, and parents will provide valuable insight to improve the effectiveness of these programs. Thus, it is hoped that this research can provide a more comprehensive view of overcoming the problem of bullying behavior among students.